Influence and Problems of Da'wah for the Preachers In Facing the Challenge of Modernization - Arwan, Arwan; Rahman, Rahman; Ghozali, Achmad; Suhaimi, Suhaimi; Saputra, Dedek (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
This article wants to explain the influence and problems of da'i for preachers in facing the challenges of modernization. Da'wah challenges in the modernization era will be increasingly difficult and complex both internally and externally. This challenge arises in various forms of modern society's activities, such as behavior in obtaining entertainment, tourism and art in a broad sense, which increasingly opens up opportunities for moral and ethical vulnerabilities to emerge.This research is a type of qualitative researchwith the library research approach as well as empirical social facts contained in the object under study and data collection techniques in the form of observation to see things that happen in the midst of society, then interpretation is carried out to draw conclusions. The results of this study explain that da'wah activities must be able to have a positive impactarising from the da'wah process. These impacts can be cognitive, affective and behavioral. Cognitive aspects can occur if there is additional knowledge, insight from the da'wah partners, affective aspects can take the form of feelings of pleasure, displeasure, likes and dislikes and changes in attitude, while behavioral aspects take the form of changes in behavior in accordance with the goals of da'wah.